Atmospheric ammonia : detecting emission changes and environmental impacts : results of an expert workshop under the Convention on Long-range Transboundary Air Pollution - Sutton, Mark A. (Springer, 2017)
Atmospheric ammonia is increasingly being recognized as a pollutant of key environmental concern. Ammonia contributes to several environmental problems, including direct toxic effects on vegetation, atmospheric nitrogen deposition, leading to the eutrophication and acidification of sensitive ecosystem, and to the formation of secondary particulate matter in the atmosphere, with effects on human health, atmospheric visibility and global radiative balance. Ammonia emissions are increasing rapidly in many parts of the world, so that these environmental concerns are expected to grow in future. In Europe, efforts are currently being made to reduce ammonia emissions, alongside reductions in other air pollutants, notably sulphur dioxide and nitrogen oxides. However, reducing ammonia emissions has proved uncertain and challenging, with only modest regional reductions achieved to date. As the emissions of sulphur dioxide and nitrogen oxides are reduced, ammonia is therefore increasingly dominating the air pollution climate of Europe and the consequent environmental impacts.